Pulse Dynamics of an All-Normal-Dispersion Ring Fiber Laser Under Four Different Pulse Regimes - Liqiang Zhang; Zhen Tian; Nan-Kuang Chen; Kenneth T. V. Grattan; Yicun Yao; B. M. Azizur Rahman; Xiaohui Li; Chengkai Yao; Haili Han; Hsiang-Chen Chui; Shien-Kuei Liaw (IEEE Access, 2020)
Based on the coupled Ginzburg-Landau equations and Jones matrices of the waveplates considered, a numerical model of an all-normal-dispersion fiber laser mode-locked by nonlinear polarization rotation has been proposed. The operating characteristics of the fiber laser discussed were studied numerically. It has been found that the proposed all-normal-dispersion mode-locked fiber laser (AND-MLFL) could deliver dissipative solitons (DSs) with a M-shaped and U-shaped spectrum, the splitting pulse with a divided spectrum and the amplifier similaritons. The evolution of the intra-cavity pulse and spectrum has been calculated under different regimes and the effects of group velocity dispersion (GVD) and nonlinearity are analyzed. When the fiber laser delivers DSs or causes pulse splitting, nonlinear effects dominate the pulse evolution. With the increase of the accumulated nonlinear phase shift, the operation states change from DS with a M-shaped spectrum to a U-shaped spectrum, and then to the splitting pulse. In the case of amplifier similaritons, both the GVD and nonlinearity play important roles in pulse evolution. The effect of nonlinear polarization rotation and filtering on the pulse reshaping has been analyzed. When the fiber laser delivers DSs with a M-shaped spectrum, the filter has a very weak effect on the pulse and on spectral reshaping. However, when the fiber laser operates in the amplifier similariton state, the filter plays a key role in pulse and spectral reshaping, whereas the nonlinear polarization rotation become less dominant. The dependence of the operational states on the filter bandwidth, fiber length, small signal gain coefficient and orientation of waveplates has also been calculated. A Yb-doped doubled-cladding fiber laser, mode-locked by nonlinear polarization rotation, has also been demonstrated and all of the four pulse regimes are obtained experimentally.